Case study: Dust in the housing of laying birds (Research, Society and Development, 2021)
As dust particles in laying poultry houses can have negative effects on health and on the environment,this study aimed to measure and compare dust concentrations in egg production sheds. The experiment was carried out in three sheds: Californian shed (G1), conventional closed shed with artificial ventilation (G2) and conventional closed shed without artificial ventilation (G3), and the birds housed were in the 22nd week of housing, in Cuité, Paraíba, Brazil.The dust particles were collected by a gravimetric pump, attached to the workers' clothes, at the height of the respiratory zone, being removed at the end of the working day. Using the evaluation methodologies (total or breathable dust) according to NIOSH (1998), weighing was performed with sample concentration calculation, then the particle size was measured by microscopy according to the methodology described by Feret(Santos, 2001), with diameter of function obtained using an optical microscope, and particles classified by size (inhalable